Effective English teachers in online EFL learning: A post-pandemic reflection on students perspectives - Fitri Agustin; Didi Suherdi; Pupung Purnawarman (Studies in English Language and Education, 2024)
In the framework of conventional academic settings, there have been a large number of studies on the qualities of effective teachers; however, studies in the context of online environments seem to be scarcely documented in the literature. This explanatory sequential mixed-method study of 224 secondary school students, 21 of whom were interviewed in detail, examined their perspectives on effective teacher characteristics in online EFL instruction. This study differed from earlier investigations of the qualities of effective teachers in terms of its research site and inquiry emphasis. The results of the surveys and interviews provided students judgments of effective teacher traits in terms of roles, professional abilities, personal qualities, and pedagogical expertise. According to the results of the polls, the most significant criteria for effective online learning management were instructors classroom management roles and their professional skills. The interviews stressed the importance of teachers qualities in managing classrooms and their pedagogical knowledge. In an online EFL instruction, students needed their teachers to scaffold them and explain what they should do with the lesson and the procedures they should follow for activities and assignments. In addition, the interviews validated teachers capacity to establish a favorable rapport with the students to facilitate their meaningful learning. As this study identified teachers professional abilities in managing online learning as a requirement, an online-learning-based professional development program for teachers is highly recommended as the most plausible alternative for the post-pandemic reflection of this current study.